2016
DOI: 10.1007/s10591-016-9381-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Neurobiology and Couple Relationship Quality: A Longitudinal Model

Abstract: Interpersonal neurobiology is an interdisciplinary theory that is being used by couple and family therapists. However, more investigation is needed to determine if this theory can accurately explain family relationships over time. In this study, we used the nationally representative National Longitudinal Study of Adolescent to Adult Health (Add Health) dataset to examine key elements of interpersonal neurobiology theory. Using structural equation modeling, we explored how maternal and paternal support and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For example, Coleman-Minahan and Samari (2020) combined Add Health data with life history interviews and found that positive father-daughter relationship quality (a composite score based on answers to scale questions including warmth, closeness, and relationship satisfaction) in Mexican-origin families was significantly linked to reduced risk of early sexual initiation. Other Add Health studies have used different terminology such as attachment, warmth, communication, or closeness, with similar positive associations (e.g., Cheshire et al, 2019;Gambrel et al, 2016). In a study of Black adolescents, perceived closeness to father figures reduced dating violence victimization for Black males and resulted in less sexual risk behavior for Black females (Alleyne-Green et al, 2015).…”
Section: Parent-child Relationship Qualitymentioning
confidence: 99%
“…For example, Coleman-Minahan and Samari (2020) combined Add Health data with life history interviews and found that positive father-daughter relationship quality (a composite score based on answers to scale questions including warmth, closeness, and relationship satisfaction) in Mexican-origin families was significantly linked to reduced risk of early sexual initiation. Other Add Health studies have used different terminology such as attachment, warmth, communication, or closeness, with similar positive associations (e.g., Cheshire et al, 2019;Gambrel et al, 2016). In a study of Black adolescents, perceived closeness to father figures reduced dating violence victimization for Black males and resulted in less sexual risk behavior for Black females (Alleyne-Green et al, 2015).…”
Section: Parent-child Relationship Qualitymentioning
confidence: 99%